Promoting Students’ Creating Innovators of the Sub-District Quality Schools under the Secondary Educational Service Area Office Bangkok 1 - Nungalee, Marisa; Wijitwanna, Somtawin (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to study and compare the opinions of the administrators and teachers about promoting students’ creating innovators of the sub-district quality schools under the Secondary Educational Service Area Office Bangkok 1, classified by personal status. The sample group consisted of 329 school administrators and teachers, selected through stratified random sampling. The research instrument was a questionnaire with a validity (IOC values) = 0.67-1.00 and a reliability value of 0.97. The data were statistically analyzed by using percentage, mean, standard deviation, t-test, One-way ANOVA, and LSD (The Least Significant Difference). The results of the research were as follows: 1) Promoting students’ creating innovators of the sub-district quality schools under the Secondary Educational Service Area Office Bangkok 1 was at a high level in the overall and particular aspects, which the highest mean aspect was Promoting the future orientation, followed by Promoting the creative thinking, Enhancing the learning opportunity, Promoting the skill of discovery, Enhancing the learning community and Enhancing the Learning environment respectively, and 2) The opinions of administrators and teachers classified by education level and school size on promoting students’ creating innovators of the sub-district quality schools under the Secondary Educational Service Area Office Bangkok 1 were significantly different at a level of .05, on the other hand, the ones also classified by gender and work experience were not different.